2010
DOI: 10.1073/pnas.0912372107
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants in phycotoxins and AChBP conferring high affinity binding and nicotinic AChR antagonism

Abstract: Spirolide and gymnodimine macrocyclic imine phycotoxins belong to an emerging class of chemical agents associated with marine algal blooms and shellfish toxicity. Analysis of 13-desmethyl spirolide C and gymnodimine A by binding and voltage-clamp recordings on muscle-type α1 2 βγδ and neuronal α3β2 and α4β2 nicotinic acetylcholine receptors reveals subnanomolar affinities, potent antagonism, and limited subtype selectivity. Their binding to acetylcholine-binding proteins (AChBP), as soluble receptor surrogates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(204 citation statements)
references
References 35 publications
10
194
0
Order By: Relevance
“…Structural studies of AChBP in complex with ligands have revealed a considerable flexibility in the so-called C-loop that closes in on agonists and forms a lid on the binding site. Thus, C-loop closure has been suggested to couple to channel activation (15,18,20,24), and it has even been suggested to be an important determinant for agonist efficacy (18,25).…”
mentioning
confidence: 99%
“…Structural studies of AChBP in complex with ligands have revealed a considerable flexibility in the so-called C-loop that closes in on agonists and forms a lid on the binding site. Thus, C-loop closure has been suggested to couple to channel activation (15,18,20,24), and it has even been suggested to be an important determinant for agonist efficacy (18,25).…”
mentioning
confidence: 99%
“…toxicity. SPx and GYM interact with both muscle and neuronal nicotinic ACh receptors (nAChR) at subnanomolar concentrations (Bourne et al, 2010;Kharrat et al, 2008), and this interaction leads to respiratory paralysis in rats and mice treated with GYM (Kharrat et al, 2008). The question that needs to be answered is whether or not this mechanism also applies to humans and thus whether the data from the MBA are suitable for risk assessment for humans.…”
Section: Azaspiracid Shellfish Poisoning (Azp)mentioning
confidence: 99%
“…The possible cause for this toxicity is the intact cyclic imine-group that some SPXs and GYMs possess (Munday 2008, Bourne et al 2010). There is evidence that the neurotoxic action of SPXs and GYMs is based on their inhibition of both muscarinic and nicotinic acetylcholine receptors (mAChR and nAChR) in the central and peripheral nervous system (Munday 2008).…”
Section: Journal Of the Hellenic Veterinary Medical Society 201162(3)mentioning
confidence: 99%